FEATURES OF THE ORGANIZATION OF THE ACCOUNTING OF OPERATIONS WITH SUPPLIED RAW MATERIALS IN THE RESOURCE POTENTIAL MANAGEMENT SYSTEM OF THE ENTERPRISE - LOPATOVSKYI, Victor; BOHATCHYK, Liudmyla; NIMCHUK , Oksana (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The distinct advantages of the organization of relations with counterparties on the terms of the contract have been identified. The approaches of domestic scientists to the interpretation of the concepts "customer-owned raw materials", "operations with customer-owned raw materials" are considered; criteria for recognition of such operations have been formed. Motives for participation in donor schemes are summarized both for the enterprise that owns the raw material and for the business entity that processes it. The most common forms of payments for the completed works on the processing of raw materials are considered. It has been proven that the organization of relations according to giving schemes should be considered only in connection with other, first of all, resource development strategies of the economic entity. It was concluded that the difficulty of carrying out operations with raw materials given at the enterprise lies, first of all, in the need to correctly reflect in the accounting the procedure for recognizing the right of ownership of the transferred raw materials and the products made from them. Solving these issues requires the business entity to properly organize the analytical accounting system and more flexible control over compliance with contract requirements. It has been established that the distinct advantages possessed by operations for processing raw materials on pre-contractual terms are able to turn this type of relationship into a flexible management tool at all stages of the production and sales cycle - from the selection of conditions and methods of receiving raw materials, to the substantiation of the most convenient forms of mutual settlements. The diversity of the implementation of davalnytny schemes makes it possible to use them in various spheres of the economy, and the presence of an appropriate system of regulatory support allows to transfer the activity of using davalnytny raw materials from the national to the international level.